ChemInform Abstract: [2, 3]‐Sigmatropic Rearrangement of Allylic Selenimides: Strategy for the Synthesis of Peptides, Peptidomimetics, and N‐Aryl Vinyl Glycines. Issue 39 (23rd September 2014) - Armstrong, Alan; Emmerson, Daniel P. G.; Milner, Harry J.; Sheppard, Robert J.
Abstract The scope of the NCS‐mediated amination/[2, 3]‐sigmatropic rearrangement of enantioenriched allylic selenides is expanded to provide access to the product classes listed in title.